Self-Actualization of the Main Character in Najib Mahfuz’s Novel Rihlatu Ibn Fattouma: A Literary Psychology Study - Subhan, Bentara; Chalis, Nur; Trisnady, Ivan Aulia (Journal of Arabic Language Studies and Teaching, 2026)
This study aims to analyze the process of self-actualization of the character Qandil in the novel Rihlatu Ibnu Fatumah by Najib mahfuz. The research method employed in this study is a qualitative descriptive method using Abraham Maslow’s literary psychology theory of self-actualization. This study utilizes written data from the novel Rihlatu Ibnu Fatumah by Najib Mahfuz that illustrates the process of self-actualization of the main character from Abraham Maslow’s perspective. The data collection methods employed in this study include reading and note-taking, literature review, close reading, and manual coding. The data in this study were analyzed using data analysis techniques involving identification, analysis, and drawing conclusions. The results of this study indicate that the character Qandil undergoes eleven stages of self-actualization according to Maslow, which include: a more efficient perception of reality, acceptance of oneself, others, and nature, a sense of social belonging, autonomy, problem-centeredness, peak experiences, the need for privacy, sustained appreciation, creativity, a democratic character structure, and deep interpersonal relationships. The researcher hopes that this study can serve as input for other research related to Abraham Maslow’s literary psychology theory.